Research in English Studies: An Interview with Gabriele Griffin - Surendra Prasad Ghimire (Indonesian Journal of Advanced Research, 2023)
In the present context, Research in English Studies has been modified and transformed with the application of digital tools and the latest developed innovative research methods. On the other hand, the postmodern philosophical worldview questioned the reliability of the data, arguments in the research, and more precisely in the findings of the whole research project (Denzin & Lincoln, 2018). In addition, the production of knowledge has been controlled by establishing various limitations and imperatives in research and publication. In such a situation, this interview was conducted with Gabriele Griffin via email for exploring the latest development in the field of research in English Studies particularly focusing on research and publication. The main objective of this interview is to unveil the contemporary research trends more importantly in the field of English Studies and to derive some of the historical development in the field of research. This interview has great significance by providing the fresh idea to the readers regarding the role of theory, production, and dissemination of knowledge